Risk of fall in hospitalized patients: risk factors and nursing interventions - Ximenes, Maria Aline Moreira (2019)
Objective: To identify risk factors for falls in hospitalized patients and propose nursing actions. Methods: This is an evaluative, descriptive and quantitative study, developed from June to September 2017, carried out in a philanthropic entity located in Sobral, Ceará, Brazil. The collection included 155 participants, being carried out using a structured instrument containing risk factors for falls, according to the taxonomy of the North American Nursing Diagnosis Association (NANDA-I). Descriptive analysis with absolute and relative frequencies was used. Results: The sample of 155 participants showed that 74.83% (n = 116) were men, 54.83% (n = 85) active workers, 62.58% (n = 97) were married, 84.45% (n = 134) Catholics and 68.38% (n = 106) had completed elementary school. The main risk factors identified were: difficulty in walking (56.77%;n= 88), impaired physical mobility (50.96%;n=79), and impaired balance (47.74%;n= 74). There was also a history of falls and the use of auxiliary devices, both with a frequency of 27.74% (n=43). As for the environment, the main risk factor was insufficient non-slip material in the bathroom, with 26.67% (n = 46). Based on these results, actions were proposed covering the cognitive and environmental dimensions, balance, transfer, the use of health devices, health education, and hospital structures. Conclusion: Difficulty in walking, impaired physical mobility, impaired balance, and use of auxiliary devices are the main risk factors mapped. The identification of the risk of falls and the prescription of appropriate nursing actions can favor the prevention of the occurrence of this adverse event in the evaluated hospital.